The CHA2DS2-VASc score for predicting atrial fibrillation in patients presenting with ST elevation myocardial infarction: prospective observational study - Aksoy, Fatih (2019)
BACKGROUND: Atrial fibrillation (AF) is the most common form of supraventricular arrhythmia following ST-elevation myocardial infarction (STEMI). The CHA2DS2-VASc and CHADS2 scores are used to estimate thromboembolic risk in cases of AF. Their usefulness in predicting the development of AF in patients pre-senting STEMI is unknown. OBJECTIVE: To evaluate the predictive value of the CHADS2 and CHA2DS2-VASc scores in patients with AF following STEMI. DESIGN AND SETTING: This prospective cohort study on 696 patients with STEMI was conducted at a tertiary-level cardiology clinic in a public university hospital. METHODS: Models including clinical and laboratory parameters were constructed to test the predictive value of CHADS2 and CHA2DS2-VASc scores. Patients were divided into two groups: with and without AF. Predictors of AF were determined using multivariate regression analysis. RESULTS: In the patients with AF, CHADS2 and CHA2DS2-VASc scores were significantly higher than in those without AF (for both P < 0.001). Factors associated with AF in multivariate analyses included CHA2DS2-VASc score (odds ratio, OR: 1.48; 95% confidence interval, CI: 1.25-1.75; P < 0.001), peak creatine kinase-myocardial binding (OR: 1.002; 95% CI: 1.00-1.003; P = 0.0024), duration of the coronary intensive care unit stay (OR: 1.69; 95% CI: 1.24-12.30; P = 0.001) and no use of renin-angiotensin system block-ers (OR: 2.16; 95% CI: 1.14-4.10; P = 0.0017). Receiver operating characteristic curve analyses showed that CHA2DS2-VASc scores were significant predictors for new-onset AF (C-statistic: 0.698; 95% CI: 0.631-0.765; P < 0.001). CONCLUSION: CHADS2 and CHA2DS2-VASc scores predicted new AF in patients presenting STEMI.